Analisis Corporate Reputation terhadap Environmental Disclosure - Husein, La Ode Maulana; Desliniati, Nurfitri (Universitas Darwan Ali, 2024)
Environmental issues that arise from various aspects of the environment make companies face challenges to be able to demonstrate responsibility for their operations. This responsibility can be seen through the sustainability report that has been required by the government, and is an important indicator to see the extent to which the company maintains the company's reputation for disclosure of its environmental aspects. Therefore, the study aims to determine the effect of corporate reputation on environmental disclosure by looking at the disclosure of the company's sustainability report. This research was conducted on 75 companies listed on the IDX with the period 2020-2022 which were selected through purposive sampling technique using data analysis techniques in the form of panel regression. The results showed that corporate reputation has no significant effect on environmental disclosure. This finding finds that the level of reputation owned by the company does not directly encourage companies to increase transparency or disclosure related to environmental issues. One of the reasons is that investors have not considered the company's environmental disclosure as an important aspect before deciding to invest. Even so, companies with a large company size have a better ability to make disclosures.